Perlindungan Hukum Klien Melalui Peran Advokat Sebagai Konsultan Hukum - Dananjaya, Adi Widhirestu (STIE Jambatan Bulan, 2026)
This research discusses the strategic role of advocates as legal consultants in ensuring legal protection for clients within Indonesia’s legal framework. Utilizing an empirical approach through observations, interviews with advocates, and examination of legal documents in selected law firms, the study highlights that advocates contribute not only through litigation but also by providing preventive and repressive legal services. The findings reveal that legal consultation helps clients to understand their rights and responsibilities while also enhancing their confidence in navigating justice mechanisms. Advocates also function as intermediaries between complex legal norms and society, improving legal awareness and a sense of security. Nevertheless, obstacles remain, particularly regarding the high cost of legal services and limited legal literacy among the public. The study concludes that advocates, when acting as legal consultants, are essential in promoting legal certainty, justice, and protection for clients.